PENDEKATAN PSIKOLOGI PERCERAIAN DALAM PENGKAJIAN ISLAM - Sholehah SN, Nur Rahmadhani; Arifi, Ahmad (University of Islam Malang, 2024)
This study aims to determine the approach to divorce psychology in Islamic studies by looking at divorce law, causes of divorce, and solutions to the consequences of problems that occur during divorce. This research uses a type of qualitative research with library research. The approach is an inductive approach. Data analysis with the Miles and Huberman method is data reduction, data presentation, verification. The results showed the psychological approach of divorce in Islamic studies that became the cause of divorce, namely (1) divorce talaq from husbands there are talaq raj'i talaq, bain talaq, Sunni talaq, bid'i talaq, and taklik talak. (2) Divorce from the claims of Fasakh, Taqlik, Shiqaq, and Khuluk's wives. The causes of divorce according to the psychological approach antalain: Pressure of family economic needs, infidelity, differences in principles, ideology or religion, family interference, and domestic violence (domestic violence). The psychological impact of children due to divorce is that they often have bad emotions that lead to very high levels of anger, temperamental personalities, quickly agitated due to uncontrolled emotions. Children whose fathers and mothers divorced showed symptoms of physical stress, had increased levels of fear and anxiety. They shut themselves off and become alone. Difficulty building relationships with others, inability to adapt to authoritative people, behavioral problems at school, bad behavior, drinking, theft, smoking, and can even fall into drugs due to the divorce of both parents. The implementation of solutions for children victims of divorce then includes Islamic therapy that must be done, namely doing prayers, reading the Qur'an, dhikr and praying. Prevention and handling of divorce, premarital education, family counseling, good communication.